Pelatihan Pembuatan Media Pembelajaran Edukatif Berbasis AI Bagi Calon Guru: ChatGPT Sebagai Solusi Pembelajaran Masa Kini - Bahtiar Bahtiar; Maimun Maimun; Nurhayati Nurhayati (Indonesian Journal of Education and Community Services, 2025)
This community service activity aims to enhance technological literacy and digital skills of prospective teachers through training on the development of educational teaching media based on Artificial Intelligence (AI), particularly using ChatGPT. The participants consisted of 35 students from the Madrasah Ibtidaiyah Teacher Education (PGMI) and Physics Education (Tadris Fisika) study programs, who took part in a series of training sessions ranging from the introduction of AI concepts and hands-on practice using ChatGPT, to the creation of instructional media products. The implementation methods included participatory approaches, hands-on practice, and collaborative project work. The results showed a significant increase in participants' understanding of AI technology and their ability to integrate ChatGPT into the development of learning materials. The participants responded very positively and expressed great enthusiasm for continuing to explore and develop AI-based teaching media in the future. This activity has made a tangible contribution in equipping future teachers with relevant competencies to meet the challenges of 21st-century education.